Multiple configuration transitions of soft actuators under single external stimulus. Issue 45 (7th November 2022) - Cao, Yanlin; Feng, Xianke; Wang, Shuang; Li, Qi; Li, Xiying; Li, Hongyuan; Hong, Wei; Duan, Huiling; Lv, Pengyu
Abstract : Multiple configuration transitions of the soft actuator can be achieved under a single external stimulus, which is synergistically contributed by geometric asymmetry, material heterogeneity, swelling ratios and geometric parameters. Abstract : Soft actuators have a wide range of applications in medical instruments, soft robotics, 3D electronics, and deployable structures, where configuration transitions are crucial for their function realization. However, most soft actuators can only morph from the initial configuration directly to the final configuration under a single external stimulus. Herein, we report a novel soft actuator by 3D printing parallel strips with crescent cross-sections onto a thin PDMS film. Multiple configuration transitions are observed when the soft actuator swells in ethyl acetate. Four factors, i.e., the geometric asymmetry of the strips, the fabrication-induced heterogeneity of the film, the differential swelling ratios of the strips and the film, and the geometric parameters of the actuator, are demonstrated to synergistically regulate the multiple configuration transitions of the actuator. Particularly, the underlying mechanisms for the configuration transitions are systematically investigated through experiments and theoretical analysis, and verified via finite element simulation. Benefitting from the multiple configuration transitions, the grasp-release-re-grab function of the actuator is demonstrated under a single stimulus. This work contributes to fundamental understanding of the morphing behaviors and the novel design of soft actuators.